“Every breath you take”: evaluating sound levels and acoustic characteristics of various neonatal respiratory support and ventilation modalities - Stummer, Sophie; Reuter, Christoph; Czedik-Eysenberg, Isabella; Bertsch, Matthias; Klebermass-Schrehof, Katrin; Mader, Johannes; Buchmayer, Julia; Bartha-Doering, Lisa; Berger, Angelika; Giordano, Vito (Frontiers in Pediatrics, 2024)
Background: Early sensory experiences have a significant impact on the later life of preterm infants. The NICU soundscape is profoundly influenced by various modalities of respiratory support or ventilation, which are often mandatory early in the care. The incubator, believed to shield from external noise, is less effective against noise originating inside. The objective of this study was to evaluate the sound levels and characteristics of frequently used respiratory support and ventilation modalities, taking into consideration the developing auditory system of premature infants. Methods: To evaluate sound dynamics inside and outside an incubator during respiratory support/ventilation, experimental recordings were conducted at the Center for Pediatric Simulation Training of the Medical University Vienna. The ventilator used was a FABIAN HFOI®. Results: Jet CPAP (Continuous positive airway pressure), whether administered via mask or prongs, generates significantly higher sound levels compared to High-flow nasal cannula (HFNC) and to High-frequency oscillatory ventilation (HFOV) delivered through an endotracheal tube. Upon evaluating the sound spectrum of jet CPAP support, a spectral peak is observed within the frequency range of 4 to 8 kHz. Notably, this frequency band aligns with the range where the hearing threshold of preterm infants is at its most sensitive. Conclusion: Non-invasive HFNC and invasive HFOV generate lower sound levels compared to those produced by jet CPAP systems delivered via masks or prongs. Moreover, HFNC and HFOV show a reduced acoustic presence within the frequency range where the preterm infant's hearing is highly sensitive. Therefore, it is reasonable to speculate that the potential for auditory impairment might be more pronounced in preterm infants who require prolonged use of jet CPAP therapy during their time in the incubator.